2020
DOI: 10.1097/md.0000000000022651
|View full text |Cite
|
Sign up to set email alerts
|

Dieulafoy disease with gastric MALT lymphoma

Abstract: Rationale: Dieulafoy lesion (DL), a rare cause of gastrointestinal bleeding, is easily covered by blood scab formation on the mucous membrane for its small size, which makes it difficult to be identified under endoscope. In clinical practice, it is also very easy to miss gastric mucosa-associated lymphoid tissue (MALT) lymphoma that exhibits atypical early manifestations under gastroendoscope and is difficult to be diagnosed by routine superficial biopsy. Most patients only experience nonspecific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It was originally approved for the evaluation of patients with gastrointestinal bleeding of unknown cause, and it is widely used for this purpose as well as for other gastrointestinal diseases ( 10 ). Zeng et al reported a case of Dieulafoy’s disease with gastric Mucosal-associated lymphoid tissue (MALT) lymphoma and found a large hemorrhage in the stomach under capsule endoscopy ( 11 ). Although producing excellent images of the upper gastrointestinal tract is challenging due to the capacious stomach and the rapid transition through the esophagus and duodenum, capsule endoscopy is a non-invasive approach for patients who are at high risk of gastrointestinal endoscopy, and it can identify patients who need conventional endoscopy for biopsy ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was originally approved for the evaluation of patients with gastrointestinal bleeding of unknown cause, and it is widely used for this purpose as well as for other gastrointestinal diseases ( 10 ). Zeng et al reported a case of Dieulafoy’s disease with gastric Mucosal-associated lymphoid tissue (MALT) lymphoma and found a large hemorrhage in the stomach under capsule endoscopy ( 11 ). Although producing excellent images of the upper gastrointestinal tract is challenging due to the capacious stomach and the rapid transition through the esophagus and duodenum, capsule endoscopy is a non-invasive approach for patients who are at high risk of gastrointestinal endoscopy, and it can identify patients who need conventional endoscopy for biopsy ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of conventional endoscopic methods may be sometimes challenging because of the location of the lesion, size, and high risk of rebleeding, which may require angiographic embolization or on rare occasions surgical intervention for definitive hemostasis (27). At present, several studies reported only small cases on the use of OTSC for Dieulafoy's lesion, and achieved a reliable clinical effect (28)(29)(30)(31)(32). Our study reported 21 patients with Dieulafoy's lesion treated by OTSC, as far as we know, which was the current maximum sample size in published studies.…”
Section: Discussionmentioning
confidence: 99%